2019
DOI: 10.3390/su11236665
|View full text |Cite
|
Sign up to set email alerts
|

A Linear Programming Model with Fuzzy Arc for Route Optimization in the Urban Road Network

Abstract: In the transport system, it is necessary to optimize routes to ensure that the distance, the amount of fuel used, and travel times are minimized. A classical problem in network optimization is the shortest path problem (SPP), which is used widely in many optimization problems. However, the uncertainty that exists regarding real network problems makes it difficult to determine the exact arc lengths. In this study, we analyzed the problem of route optimization when delivering urban road network products while us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…According to the papers mentioned above, numerous studies have shown that one of the main weaknesses of the performance-optimization models used by many companies is that they have adopted a single-dimensional focus. Thus, the optimization created in this paper starts from a multidimensional vision of performance, being consistent with the current studies [11][12][13][14]20].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…According to the papers mentioned above, numerous studies have shown that one of the main weaknesses of the performance-optimization models used by many companies is that they have adopted a single-dimensional focus. Thus, the optimization created in this paper starts from a multidimensional vision of performance, being consistent with the current studies [11][12][13][14]20].…”
Section: Discussionmentioning
confidence: 62%
“…In areas such as transportation, methods such as AHP, TOPSIS, and PROMETHEE [6] have been used for optimization or a mixed-integer linear-programming model [14]. Combined methods of MCDM, such as AHP and TOPSIS, were used by the authors of [21] for product ranking using customers' reviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, FLP has been used in areas such as finance, energy, and transportation [9][10][11][12][13][14][15]. In the literature, no study has been found in which FLP has been compared with classical LP in the demand forecasting problem of a maketo-stock company.…”
Section: Introductionmentioning
confidence: 99%